Sinonasal Inverted Papilloma: Prognostic Factors with Emphasis on Resection Margins - Lin, Giant C. (Georg Thieme Verlag KG, 2014)
Objective We review our institution's experience with the treatment of inverted papilloma (IP) with emphasis on the implications of surgical margins for disease control. Design Retrospective chart review of patients with IP treated at the University of Michigan from 1996 to 2011. Setting Tertiary care center. Participants Patients undergoing surgical resection with curative intent for IP. Main Outcome Measures Overall survival, disease-specific survival, and locoregional control were used as main outcome measures. Results We studied 129 patients including 19 with carcinoma arising from IP. Disease-free rates at 2, 3, and 5 years were 79.7%, 77.9%, and 61%, respectively. Overall, 10 of 18 recurrences were detected > 2 years from follow-up, with recurrences detected up to 8 years from surgery. For benign disease, obtaining tissue margins outside of the primary specimen for margin control did not affect disease control rates. Conclusion IP is a disease that requires significant follow-up periods beyond 2 years. For IP without carcinogenesis, acquiring margins outside of the tumor specimen did not appear to affect disease control rates in this study. No clear predictors of malignancy were seen in this study, which highlights the need for further research to predict this phenomenon.